Landscape areas within fortified medieval-renaissance : towns typology, valorisation and enhancement = Pejsažne površine unutar utvrđenih srednjovjekovno-renesansnih gradova : tipologija, vrjednovanje i unaprijeđenje - Obad-Šćitaroci, Mladen (Array, 2020)
The research was focused on determining the types of landscape areas within the fortifications of medieval-Renaissance towns based on the use and the criteria for their valorisation and enhancement. Twenty-six Mediterranean and west European towns were analysed. Nine types of landscape areas and seven valorisation criteria have been determined. Three current approaches to the use of landscape areas within the town walls have been recognised.